2021
DOI: 10.3390/cryst11121439
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Solidification of Sandy Soil by Microbially Induced Carbonate Precipitation (MICP)

Abstract: Microbially induced carbonate precipitation (MICP) is a promising technology for solidifying sandy soil, ground improvement, repairing concrete cracks, and remediation of polluted land. By solidifying sand into soil capable of growing shrubs, MICP can facilitate peak and neutralization of CO2 emissions because each square meter of shrub can absorb 253.1 grams of CO2 per year. In this paper, based on the critical review of the microbial sources of solidified sandy soil, models used to predict the process of san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 160 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…Various factors affect the calcium carbonate formation pathway and bacterial performance including the type of bacteria, concentration of microorganisms, calcium ratio, presence of nucleation sites, enzymatic activity, temperature, grouting method, injection flow rate, pH, presence of nutrients, and calcium ions in the environment [ 4 , 19 , 21 , 22 , 24 ]. Different species of bacteria require different conditions for growth and reproduction, but for most, the optimal conditions are as follows: temperature 20–37 °C, pH 6.5–9, curing time—14 days, concentrations of urea and calcium ion—0.5 mol/L, injection frequency—once per day [ 4 , 19 , 21 , 22 , 25 , 26 ].…”
Section: Existing Methods Of Soil Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors affect the calcium carbonate formation pathway and bacterial performance including the type of bacteria, concentration of microorganisms, calcium ratio, presence of nucleation sites, enzymatic activity, temperature, grouting method, injection flow rate, pH, presence of nutrients, and calcium ions in the environment [ 4 , 19 , 21 , 22 , 24 ]. Different species of bacteria require different conditions for growth and reproduction, but for most, the optimal conditions are as follows: temperature 20–37 °C, pH 6.5–9, curing time—14 days, concentrations of urea and calcium ion—0.5 mol/L, injection frequency—once per day [ 4 , 19 , 21 , 22 , 25 , 26 ].…”
Section: Existing Methods Of Soil Improvementmentioning
confidence: 99%
“…The CaCO 3 deposition is not uniform and most of it is deposited near the injection point, which consequently leads to the appearance of bioplugging, the phenomenon of the inability to penetrate fine sandy and silty soils due to clogging in the void space in the upper layers of the soil [ 25 , 34 , 35 ].…”
Section: Existing Methods Of Soil Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Li accelerated sand fixation and mitigated desertification through revegetation and ecological restoration by combining microbial mineralization with SCB technology [ 173 ]. Gao and Zhang et al [ 174 , 175 ] induced microbial growth by soybean extract and added Mg to the medium for desertification control in a desert area of northwest China, so as to further benefit ecosystem reconstruction. On the basis of frequent seawater inundation and erosion of coastal dunes ascribed to extreme weather and accelerated sea-level rise, researchers have treated wave-attacked dunes with microbial and enzyme-induced calcium carbonate precipitation, discovering that the mineralization effect can be effective in reducing dune erosion.…”
Section: Mineralization Application Areasmentioning
confidence: 99%
“…Studies have shown that the use of low-pH MICP [21,22], struvite precipitation [23], and calcium phosphate biocement [22,24] is more effective in reducing the amount of ammonia produced. More research on ammonium ion-removal methods is needed in the future to promote the application of MICP [25]. Modifying low-permeability clay soil via MICP mixing and sample making is practical; however, granite residual soil is fundamentally different from clay and silt in the aspects of particle size distribution, microstructure and pore characteristics.…”
Section: Introductionmentioning
confidence: 99%